Decoding Cultural Affinity in Video Games: An Examination of Narrative Expression, Visual Aesthetics, and Interactive Design in the Digital Era - Vindigni, Giovanni (Advances in Social Sciences Research Journal, 2023)
Academic discourse and studies have investigated the interplay between video games and cultural heritage, concerning how cultural values link digital transformations with traditional narratives in the form of a convergent structure [1; 2; 3; 4; 5; 6]. According to Champion [1], Borowiecki and Prieto-Rodriguez [6], video gaming is a contemporary digital medium that amplifies the expression of storytelling and allows users to serve as both drama performers and audience members. In addition, video games reflect the cultural aspects of society through visual aesthetics, where architectural features, the cutting-edge culture of video game casts, and iconographic landscapes depict the elements of contemporary art [7]. Game theory is a theoretical framework that helps study the cooperation and conflict among diverse agents identified as players representing different cultural aspects [8; 9; 10]. Conversely, Warmelinks’ [11] online game interactivity theory will aid in addressing how different designs and interactivity aspects of players, games, and the computer reflect cultural affinity in video games [12; 13; 14]. This article conducts a theory- and investigator-triangulation survey of cultural affinity in video games by addressing the polysemous aspects with regard to theoretical discourse. The article will also focus on the question of whether, in the view of international system-theoretical discourse in the social engineering context, contextual factors that may be falsified abductively are present, thereby leading to negative connotations. Lastly, the article will explain the product-specific status of the video game industry and the video game product as captured in both academic discourse and practise.